Access to materials on Malay world studies from Leiden to Bangi: A model for information repackaging on the information superhighway - Ding, Choo Ming (Universiti Kebangsaan Malaysia, 2004)
The aim of this paper is to outline the history of Dutch scholarship on the Malay World and to elaborate on reasons for developing a single-articlecollection at ATMA. Some 300 years ago, Dutch scholars embarked on creating the discipline of Malay studies, founding research institutes, producing journals and books, and developing library collections. Today, despite the revolution in information technology that has witnessed an explosive interest in full-text databases, databases on Malay World Studies are extremely rare. In view of this scarcity, we at ATMA have been prompted to develop a singlearticles- collection aimed primarily at meeting the growing needs of researchers for a full-text service. This represents a paradigm shift from the conventional blanket collection development practised in libraries throughout the world